Musing on Ruins in Edward Daniel Clarke’s Home Tour - Carmen-Veronica Borbély (Babel: Littératures Plurielles)
This study examines Edward Daniel Clarke’s “Letters on Travel” and his 1791 domestic tour as examples of travel writing that anticipate what Virgil Nemoianu defines as Biedermeier or secondary Romanticism and that promote distinctive approaches to ruins and the emotions they generate in viewers. These emotions range from the intensely cerebral inquisitiveness that drives Clarke’s archaeological inquiries to the somewhat dismal thrills of his antiquarian discoveries, and from the anguish caused by what he foresees as the inevitable dissolution of history’s material traces to the comic relief he injects into scenes of melancholy confrontation with ghostly remainders of bygone times.